Structures of Werner clathrates - Taylor, Michael William (Department of Chemistry, 2016)
This work is predominantly devoted to the 4-phenylpyridine ligand and the role that it plays in the formation of a series of inorganic coordination complexes termed Werner Clathrates. The synthesis and characterization by single crystal X-ray diffraction techniques are reported for 18 structures, the majority of which, upon crystallization, have the ability to include solvent or guest molecules within the host framework. The compounds are divided into four broad classes with the host complex of each as follows: Class A [Ni(NCS)₂(4-PhPy)₄]; Class B [NiCl₂(4-PhPy)₄]; Class c [Ni(NCS)₂(4-MePy)₂(4-PhPy)₂]; Class D [NiX₂(dmso)₂(4-PhPy)₂] where X= Ncs- or Cland [Ni(NCS)₂(4-RPy)₄] where R = 4-t-Bu or 4-Bz. The guest molecules, anionic ligand and substituent on the pyridine ligand have all been varied to try to establish the role that they each play in the formation of a structure. Much effort has been spent on the location and refinement of disordered guest molecules. Use has been made of statistical disorder and molecular scattering factors to try and successfully model these guests. The shapes of the cavities containing the guest molecules have been mapped by volume calculations and comparisons made between the packing of the compounds. Several of the complexes pack in space groups which are subsets of others and attempts have been made to determine the cause of the reduction in symmetry. A new technique to analyze competition experiments, with two guest solvents competing for occupation of the voids within the host lattice, has been established. Preliminary results for competition between p-xylene/benzene, p-xylene/toluene and p-xylene/ethylbenzene with the host complex [Ni(NCS)₂(4-ViPy)₄] are reported. The ability of the host complex [Ni(NCS)₂(4-MePy)₂(4-PhPy)₂] to separate a series of straight chain alcohols is demonstrated. The preference, by this host complex, for guest molecules containing a linear skeleton of 5 non-hydrogen atoms, is explained in terms of potential energy and residual volume calculations. Thermal analysis, consisting of thermogravimetry and differential thermal analysis, has been performed on several of the compounds. Temperatures of guest release, host decomposition and the enthalpies involved at each of these steps are reported.